Wonderstruck : A Novel in Words and Pictures - Selznick, Brian (New York : Scholastic Press, 2011)
Having lost his mother and his hearing in a short time, twelve-year-old Ben leaves his Minnesota home in 1977 to seek the father he never knew in New York City, and meets there Rose, who is also longing for something missing from her life.
Includes bibliographical references (p. 635-637).
Keywords: American Museum of Natural History -- Fiction; Family life -- Fiction; Diorama -- Fiction; Deaf -- Fiction; Physically handicapped -- Fiction; Museums -- Fiction; Runaway children -- Fiction; New York (N.Y.) -- Fiction -- History -- 20th century